Feasibility, usability and acceptability of a lifestyle-integrated multicomponent exercise delivered via a mobile health platform in community-dwelling pre-frail older adults: a short-term, mixed-methods, prospective pilot study - Na Li; Chuxin Liu; Nan Wang; Siyang Lin; Yin Yuan; Feng Huang; Pengli Zhu (BMC Geriatrics)
Abstract Background Pre-frailty is a window of opportunity for frailty reversal and can be enhanced by multicomponent exercise. The Lifestyle-integrated Functional Exercise (LiFE) program may be a promising alternative to overcome traditional exercise barriers. The latest advancements in mobile health (mHealth) technology have enabled individuals to retain the advantages of supervised exercise training within group settings while providing exercise programs that can be accessed and completed at home. This study aims to assess the feasibility, acceptability, and primary efficacy of the PF-Life program, which is the Lifestyle-Integrated Functional Exercise program for Pre-Frail supported by an mHealth platform. Methods Sixteen pre-frail adults aged ≥ 65 years were recruited from five community health centers in Fuzhou, China. All participants were prescribed the PF-Life program by geriatricians using the mhealth platform (web-based portal). Participants engaged in the customized exercises program following in-app video instructions and feedback on the mhealth platform (smartphone application). Physical activity (PA) and sedentary behavior (SB) were registered daily through wearable devices. Study endpoints were feasibility (retention rate, compliance rate, adverse events), usability (system usability scale), acceptability (qualitative interviews), changes in physical function (timed up and go (TUG), handgrip strength (HGS), and 30-second chair rise tests), PA and SB. Results The intervention was feasible, 88% of participants adhered completely to the study protocol, and 95% had completed at least 75% of the prescribed experimental duration. System usability was high (85 out of 100 best imaginable). Changes were observed from baseline to follow-up for total HGS (21.41 ± 6.38 vs. 24.12 ± 6.62 kg, P < 0.05, d = 0.714), TUG (8.23 ± 1.33 vs. 7.48 ± 2.01 s, P < 0.01, d = 1.647) and 30-second chair rise test (17.13 ± 4.3 vs. 20.04 ± 4.54 repetitions, P < 0.01, d = 0.94). In addition, SB decreased by a mean of 33 min/day (P < 0.01), and low physical activity increased by 31 min/day (P < 0.01). No adverse events occurred. The majority of participants found the PF-Life program to be straightforward, adaptable, and easily integrable into their daily routines. Conclusions Preliminary studies have demonstrated that the PF-life program exhibits good compliance, safety, and usability for the pre-frail elderly population. Large-scale randomized controlled trials are required to ascertain its long-term effectiveness.